Goldilocks and the three bears - Alperin, Mara; Daubney, Kate (London Little Tiger Press, 2014)
When Goldilocks sneaks into the three bear$1 (Bs cottage, no one seems to be home. But the bears soon return from their walk... Will they catch that naughty little girl?s
English stories
1 2 13 23
Keywords: Fairy tales; Folklore -- England; English stories